The Analysis of Students Needed in Digital Teaching Media - Sartika, Septi Budi; Suyidno; Akbar Wiguna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Digital teaching media has become an integral part of education in the industrial era 4.0, but most schools have not facilitated it properly. This study aims to analyze students' needs for digital learning media. This study is a cross-sectional survey research, where 661 junior high school students in East Java were involved in filling out a digital teaching media needs survey questionnaire. Based on the results of the analysis, digital learning media is needed by students, especially to make it easier for them to learn science material, make learning more fun, and increase motivation and science learning outcomes. Thus, the media needs to be implemented at the education level.